The Influence of Locality on Customer Satisfaction at Manhattan Hotel Jakarta - Suesilowati, Suesilowati; Fauziah, Alisa Sandra; Frisiska, Frisiska (International Journal on Advanced Science, Education, and Religion, 2025)
The high surge in demand for accommodation has led to hotels in Indonesia being required to provide maximum service and a memorable experience for tourists. The strategy employed is to integrate local elements into various aspects of hotel services. One hotel with the potential to implement this strategy is the Manhattan Hotel Jakarta. Its strategic location makes it a potential showcase for Betawi culture and other Indonesian cultures. However, the integration of local elements into hotel services has not been fully realized, as evidenced by guest reviews on online platforms such as Google Reviews and TripAdvisor. Some guests even expressed their hopes for a stay experience with a touch of local culture. This study examines the influence of local elements on customer satisfaction at the Manhattan Hotel Jakarta. This study uses an associative quantitative approach with data collection through questionnaires from 90 respondents who are visitors to the Manhattan Hotel Jakarta. The data was analyzed using simple linear regression to see the effect of one variable X on variable Y through the SPSS application. The results of this study show that there is an effect of locality (X) on guest satisfaction (Y) at the Manhattan Hotel Jakarta. The correlation coefficient (R) test yielded a value of 0.736, indicating a positive relationship between variables X and Y. The R² determination test produced a value of 54.2%, indicating that the local factor (X) influences guest satisfaction (Y) at the Manhattan Hotel Jakarta by 54.2%.